"And Other Duties as Assigned": Expanding the Boundaries of the E- resource Lifecycle to Get Things Done. Issue 1 (18th May 2016) - Lesher, Marcella; Fowler, Stacy; Tovstiadi, Esta
Abstract : This presentation focused on how elements of the electronic resource lifecycle, such as those described in the NASIG Core Competencies for Electronic Resource Librarians and the Techniques for Electronic Resource Management, apply to the management of physical library projects, including the weeding and shifting of physical collections, a digitization project, as well as other "duties as assigned" that are part of the average librarian's workload at a small library. Additionally, this presentation touched on issues related to managing print and electronic collections in law libraries.